Reversed sex disparities in heart failure mortality in Spain, 2000–2023: a population-based analysis of older adults - Hurtado-Prieto, Ángela; Mariscal-López, Eloísa; Gutierrez-Bedmar, Mario; López-Gigosos, Rosa (Frontiers in Public Health, 2025)
Background and objectivesHeart failure (HF) is a growing public health concern in Spain, ranking as the third leading cause of cardiovascular mortality and contributing substantially to hospitalizations and outpatient visits. Clinical presentation, pathophysiology, therapeutic response, and healthcare access differ significantly between sexes. This study analyzes trends in HF mortality in Spain from 2000 to 2023, with a specific focus on sex-based disparities.MethodsWe conducted a population-based descriptive analysis of annual HF mortality among individuals aged 50 and older in Spain, disaggregated by sex and five-year age groups. Mortality trends were examined over two periods (2000–2008 and 2009–2023) to assess patterns of change over time.ResultsOverall, HF mortality has declined in Spain, with a sharper reduction from 2000 to 2008, followed by a more gradual decrease in subsequent years. Women exhibited a 34.4% higher average HF mortality rate compared to men, although this gap narrowed significantly over the study period. Age-stratified analysis revealed higher HF mortality in men aged 50–79, while in those aged 80 and older, women exhibited higher mortality.ConclusionPersistent sex disparities in HF mortality underscore the need for gender-sensitive approaches to cardiovascular disease prevention, diagnosis, and treatment. Public health policies must prioritize HF and integrate sex-specific considerations to address inequities and improve outcomes for both women and men.